Medico-Social Approach to the Development of a Methodology for Assessing the “Quality of Life” after Cataract Phacoemulsification. Part 2 - I. G. Ovechkin; N. I. Ovechkin; A. V. Shakula; A. I. Pavlov; D. F. Pokrovsky (Oftalʹmologiâ, 2022)
Purpose. Development of the final version of the “quality of life” (QoL) questionnaire for a patient after cataract phacoemulsification (PEC) based on an expert assessment by ophthalmologists.Methods. According to the results of the previously completed stage of work, 35 possible complaints of the patient were identified. The study was performed with the participation of 47 expert ophthalmologists with professional experience from 7 to 35 years (average 19.2 ± 1.4 years), including experience in performing PE from 1 to 24 years (average 11.9 ± 1. 7 years). Each of the experts performed three main tasks: analysis of the primary version of the questionnaire for adding and (or) correcting questions; assessment of the relevance of each of the questions from the standpoint of the degree of influence on the patient’s QoL (0 points — the question is not relevant; 10 points — the question is very relevant); assessment of the “severity” of the complaint in terms of the frequency of occurrence (in the range from 10 points — the occurrence of a symptom does not determine the severity of the disease, to 0 points — the occurrence of a symptom determines the highest severity of the disease). At the same time, the following scaling procedure was used: “Practically no problems” (occur during 0–4 % of the patient’s total active time), “Mild problems” (5–24 %), “Moderate problems” (25–49 %), “Severe problems” (50–95 %), “Absolute problems” (96–100 %). “Virtually no problems” was indicated as 10 points.Results. As part of the solution of the first task, the number of questions was increased from 35 to 52. Mathematical analysis of the results of the second task was carried out on the basis of calculating the basic parameters of descriptive statistics for all 52 questions — the arithmetic mean (as a “weight” coefficient of the question) and standard deviation (as indicator of consistency of the position of the respondents). Subsequently, the “ejection” of insignificant questions was performed (according to the Pareto method with 80 % of the “pool” of questions with the maximum contribution to relevance), as well as the clinical association of similar questions and the assessment of statistical validation (feasibility) of such an association.Conclusion. An expert assessment of ophthalmologists confirmed the validity of using the “social model” of health based on the development of “domains” of the international classification of functioning when developing the QoL questionnaire after FEC. The final version of the «FEC-22» questionnaire fully complies with the content validity requirements.